2010
DOI: 10.1162/jocn.2009.21313
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine, Paranormal Belief, and the Detection of Meaningful Stimuli

Abstract: Dopamine, paranormal belief, and the detection of meaningful stimuliKrummenacher, P; Mohr, C; Haker, H; Brugger, P Krummenacher, P; Haker, H; Brugger, P (2010 Abstract ■ Dopamine (DA) is suggested to improve perceptual and cognitive decisions by increasing the signal-to-noise ratio. Somewhat paradoxically, a hyperdopaminergia (arguably more accentuated in the right hemisphere) has also been implied in the genesis of unusual experiences such as hallucinations and paranormal thought. To test these opposing assum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
87
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(100 citation statements)
references
References 106 publications
10
87
3
Order By: Relevance
“…Krummenacher, Mohr, Haker, & Brugger, 2010;Rogers et al, 2009;Watt & Wiseman, 2002). Overall we found evidence that skeptics outperformed believers on four measures that require some form of analytical thinking: (1) the logic subscale of the Shipley Institute of Learning Scale, which required them to complete patterns of words, letters, and numbers; (2) the remote associations task, which required the identification of a nonpresented word that was related to three presented words; (3) the rejection of conspiracies on the conspiracy questionnaire, suggesting that skeptics engage in more critical or analytical thinking about these kinds of conspiracies than do believers; and (4) the argument evaluation task, which requires critical thinking about the quality of arguments made during a hypothetical debate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Krummenacher, Mohr, Haker, & Brugger, 2010;Rogers et al, 2009;Watt & Wiseman, 2002). Overall we found evidence that skeptics outperformed believers on four measures that require some form of analytical thinking: (1) the logic subscale of the Shipley Institute of Learning Scale, which required them to complete patterns of words, letters, and numbers; (2) the remote associations task, which required the identification of a nonpresented word that was related to three presented words; (3) the rejection of conspiracies on the conspiracy questionnaire, suggesting that skeptics engage in more critical or analytical thinking about these kinds of conspiracies than do believers; and (4) the argument evaluation task, which requires critical thinking about the quality of arguments made during a hypothetical debate.…”
Section: Discussionmentioning
confidence: 99%
“…Some research suggests that paranormal believers are more likely to identify patterns in noise or draw meaningful connections between unrelated events (Blackmore, 1992;Krummenacher et al, 2010;Rominger, Weiss, Fink, Schulter, & Papousek, 2011). For example, when presented with images composed of visual noise, Blackmore and Moore (1994) found that psychic believers were significantly more likely to see patterns in the noise than skeptics (see also Riekki et al, 2013;van Elk, 2013).…”
Section: Implications and Future Directionsmentioning
confidence: 99%
“…Specifically, both madness (i.e., psychosis) and genius (i.e., high creativity) have been linked to a hyperactive RH, where facilitated formation of abnormal associations could stimulate both delusional and creative ideas (Bracha 1989;Leonhard and Brugger 1998;Pizzagalli et al 2001;Taylor et al 2002;Krummenacher et al 2010). This notion is supported by studies showing that individuals expressing positive schizotypical traits, that is, schizophrenia-like thought patterns and perceptions including odd beliefs, paranormal thoughts, and unusual perceptual experiences, display increased associative processing Mohr et al 2001Mohr et al , 2006, specifically in the RH, as assessed through a lateral semantic priming task , and increased creativity (Leonhard and Brugger 1998;Weinstein and Graves 2002;Folley and Park 2005;Nettle and Clegg 2006;Acar and Sen 2013).…”
Section: Hemispheric Reward Asymmetry and Hemispheric Asymmetries In mentioning
confidence: 99%
“…Dopaminergic activity has also been associated with personality traits such as reward susceptibility (18), which partially predicts the magnitude of PA (18,19). More recently, the personality dimension of magical thinking (MT), which is thought to be related to dopaminergic function (20), has been implicated in modulating expectation-related lateralized PA in healthy adults (21). MT -the belief that one can bring about a circumstance or event by thinking about it or wishing for it -is a fundamental dimension of a child's thinking (22,23).…”
Section: Introductionmentioning
confidence: 99%
“…MT -the belief that one can bring about a circumstance or event by thinking about it or wishing for it -is a fundamental dimension of a child's thinking (22,23). MT in healthy adults has been frequently associated with enhanced meaning attribution (20) and it has been shown to facilitate associative, possibly right hemisphericmediated processing (24,25). Indeed, a right hemisphere dominance has been suggested for MT (26) and for pain processing -albeit with inconsistent findings (27,28).…”
Section: Introductionmentioning
confidence: 99%